Survey of Developing of Assistance Unit for Research Processing - Widyasari (TOPAZART, 2023)
Higher education institutions play a vital role in cultivating skilled professionals through activities like research and publications. Lecturers and students are expected to engage in these endeavors, with lecturer performance often gauged by regular publications. However, the demanding nature of research and publication activities can strain some universities and cause them to need more support. This survey aims to gain the answer why students and lecturers need a research-assisted unit and the necessity for a Publication and Research Assistance Unit in higher education, anticipating that such a unit would enhance the quality and quantity of research and publications by providing essential support to lecturers and students. This study uses a qualitative research method to process data using NVivo with four steps: Gathering information, coding, running queries, and reporting. The results show why the assisted research unit is essential.